Voz do ator: condições ambientais e de organização de trabalho - Souza, Guilherme Zaramella de (2016)
Introduction: The number of Speech Therapy publications regarding professional voice has recently grown noticeably. Differing from other voice professionals, though, not many protocols have been established to assess Actor’s vocal productions. Objective: Analyse environmental and organisational conditions for working actors, associating the former two to vocal symptom references. Method: One hundred actors with a theatrical experience of at least two years answered an adapted version of a survey named Condição de Produção Vocal do Professor (CPV-P) / Teacher’s Vocal Production Conditions which was conceived by experienced voice research professionals. The survey focused on environmental, organisational and functional aspects of actor’s voice production. All data was submitted to descriptive statistical analysis. For the "vocal symptoms" outcome analysis between independent variables the chi-square test was used. A multiple binary logistic regression analysis (p<0,05) was employed to some outcomes. Results: Amongst the respondents, 56% are male, average age of 30.8 years (sd = 8.6), 49% can’t provide for themselves with acting alone and resort to complimentary activities, often also vocally demanding. Phlegm was the primary symptom to be exposed (68.0%), followed by throat dryness (54.0%) and deep voice(45.0%). There was also a significant statistical link between stressful work rhythm, psychological abuse and weakened voice (p=0.030 and p=0.048 respectively). Actors mindful of health-impacting work issues relied on that as a protective factor to secretory coughing (OR=0.40; p=0.044), dry throat (OR=0.42; p=0.042) and hoarseness (OR=0.30; p=0.011). Shortness of breath was manifested as a symptom in a lower incidence amongst actors who habitually cool-down their voices (OR=0.19; p=0.034). Conclusion: Dust and noise were pointed as the main environmental issues whilst intense physical exertion and stressful work rhythm were pointed as organisational ones. The most prevalent symptoms were phlegm, dry throat, deep voice and dry cough. In this context phlegm was directly associated with noise